Case report: Atypical neurofibromatous neoplasm with uncertain biological potential of the sciatic nerve and a widespread arteriovenous fistula mimicking a malignant peripheral nerve tumor in a young patient with neurofibromatosis type 1 - Grübel, Nadja; Antoniadis, Gregor; König, Ralph; Wirtz, Christian Rainer; Bremer, Juliane; Pala, Andrej; Reuter, Melanie; Pedro, Maria Teresa (Frontiers in Oncology, 2024)
We report an unusual constellation of diseases in a 32-year-old female with neurofibromatosis type 1 (NF1) diagnosed with the recently described precursor entity of malignant peripheral nerve sheath tumor (MPNST)-so-called Atypical Neurofibromatous Neoplasm with Unknown Biological Potential (ANNUBP) and a large symptomatic cervical arteriovenous fistula.An  18 F 2-Fluoro-2-deoxy-D-glucose PET/CT (FDG-PET/CT) was performed to detect and stage a conspicuous symptomatic cervical tumor. The FDG-PET/CT showed high FDG-uptake in one of the multiple known tumorous lesions associated with peripheral nerves. However, no relevant FDP-uptake was observed in this affected cervical area. After digital subtraction angiography, the cervical mass turned out to be a widespread arteriovenous fistula of the vertebral artery. This was successfully treated using endovascular embolization. Subsequently, magnet resonance imaging (MRI) of the FDG-positive tumor revealed a well-enhanced homogeneous mass of the sciatic nerve measuring 5.2x2.4x2.8 centimeters.Microsurgical gross total tumor resection was performed using ultrasound. The final histopathological diagnosis was ANNUBP transformed from neurofibroma. The patient benefited excellently from the surgery; no recurrence or metastasis has been observed since resection. According to imaging, ANNUBP can be characterized as a well-enhanced homogeneous mass on MRI, displaying high uptake on FDG-PET/CT and hypoechogenic in ultrasound.